Exploring the Impacts of the Introversion Personality Traits on Algerian EFL Students’ Oral Proficiency: First Year BA Students at IbnKhaldoun University-Tiaret as a Sample - Benabed, Ammar (Technium Social Sciences Journal, 2022)
EFL students, in particular, have a tough time mastering the many parts of speaking skills. The purpose behind the current study is to examine the many impacts of introversion. Furthermore, the primary goal of this endeavor is to determine the level of oral competency of introverted students in a classroom. To do so, a mixed methodological approach is adopted to test the put forward hypotheses and uncover the answers to the research questions. To gather valid data, a questionnaire was handed out to 100 first year BA students, and a structured interview was conducted with 3 tenured and experienced EFL teachers. A descriptive analysis was also employed to examine the collected data. The findings have shown that reserved and introverted students struggle too much during oral sessions .speaking performance suffers when they are more reserved or introverted.